Don't be silly, Mr. Twiddle! - Blyton, Enid (Bounty Books London, 2014)
Mr Twiddle is a kind old soul with the best intentions, but he is extremely forgetful, very lazy and more than a little bit silly. In this story he gets caught up in a giant snowball